2018
DOI: 10.1073/pnas.1804428115
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping, transcriptomics, and transient expression identify candidate genes mediating plant–pathogen interactions in a tree

Abstract: SignificanceInternational trade has resulted in the introduction of plant diseases into natural ecosystems around the world. These introductions have potentially catastrophic impacts on ecosystem structure and function. Leveraging genomic tools, natural variation within a tree species, and a high-throughput phenotyping platform, we present a framework that can be broadly applied to rapidly identify candidate genes associated with resistance and susceptibility to introduced plant diseases. The unprecedented spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 37 publications
5
74
0
Order By: Relevance
“…To reveal the population structure, genetic divergence, and signatures of natural selection, whole-genome resequencing studies have been performed in some forest trees, such as poplar ( Slavov et al , 2012 ; Evans et al , 2014 ), eucalypt ( Silva-Junior et al , 2015 ; Silva-Junior and Grattapaglia, 2015 ), and oak ( Ortego et al , 2018 ). Furthermore, the causal genes underlying phenotypic variation, particularly for biomass traits, wood properties, ecological traits, and pathogen resistance, have been explored through genome-wide association studies (GWAS) ( Porth et al , 2013 ; McKown et al , 2014 ; Muchero et al , 2018 ). Benefiting from rapid genotyping using high-throughput sequencing technology, whole-genome resequencing also provides an efficient strategy for detecting nucleotide variation, exploring the demographic history, and elucidating genetic architecture of seed salinity tolerance of P. euphratica .…”
Section: Introductionmentioning
confidence: 99%
“…To reveal the population structure, genetic divergence, and signatures of natural selection, whole-genome resequencing studies have been performed in some forest trees, such as poplar ( Slavov et al , 2012 ; Evans et al , 2014 ), eucalypt ( Silva-Junior et al , 2015 ; Silva-Junior and Grattapaglia, 2015 ), and oak ( Ortego et al , 2018 ). Furthermore, the causal genes underlying phenotypic variation, particularly for biomass traits, wood properties, ecological traits, and pathogen resistance, have been explored through genome-wide association studies (GWAS) ( Porth et al , 2013 ; McKown et al , 2014 ; Muchero et al , 2018 ). Benefiting from rapid genotyping using high-throughput sequencing technology, whole-genome resequencing also provides an efficient strategy for detecting nucleotide variation, exploring the demographic history, and elucidating genetic architecture of seed salinity tolerance of P. euphratica .…”
Section: Introductionmentioning
confidence: 99%
“…However, the QTL did contain a tandem repeat of a G‐type lectin receptor‐like protein kinase that was expanded in P. deltoides . This protein could play a similar role to a receptor‐like kinase from the same family (Yang et al, 2016) that was associated with susceptibility to S. musiva in the P. trichocarpa study (Muchero et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…This is not the first case of potential novel alleles being important in resistance to biotic stress. In a P. trichocarpa GWAS population, three genes have been found that confer novel resistance to S. musiva canker infection and an additional single gene that, when inherited, can suppress that resistance (Muchero et al, 2018). Although cases such as this are still under investigation to understand mechanisms of novel resistance, it can also originate from a variety of simple traits inherent to a non‐native species such as delayed emergence due to phenology (Mercader, Aardema, & Scriber, 2009) or changes in secondary metabolites that are important cues in insect recognition of the host important in oviposition (Nahrstedt, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The barrier of entry for using CRISPR/Cas9 to engineer resistance to these pathogens is particularly low for two reasons, the first being that CRISPR/Cas9 protocols have already been established in Populus species ( Fan et al., 2015 ; Zhou et al., 2015 ). The second reason is that candidate genes associated with resistance have already been identified for both Melampsora and Sphaerulina species ( Yin et al., 2004 ; Duplessis et al., 2009 ; La Mantia et al., 2013 ; Muchero et al., 2018 ). As discussed previously, there have now been a number of studies using CRISPR/Cas9 in Populus species, and while two of these studies used CRISPR/Cas9 to explore the functions of genes in Melampsora resistance by creating knockout mutants ( Jiang et al., 2017 ; Wang et al., 2017 ), none of them used CRISPR/Cas9 to directly engineer disease resistance.…”
Section: Future Perspectives For Crispr/cas9 In Forest Pathologymentioning
confidence: 99%